Exploring the Odonata diversity in the Chaco ecoregion (Northern Argentina) - Molineri, Carlos (2023)
During 2021 and 2022, 33 localities mostly in the Dry Chaco ecoregion from Argentinawere assessed for Odonata diversity. We registered 84 species, about 29% of the totalrichness known for Argentina. We reared 14 species from larva to adult, two of which arestill unknown at the larval stage (Progomphus aberrans Belle and P. kimminsi Belle). Wealso report 13 new provincial records: Orthemis aequilibris Calvert, Brachymesia furcata(Hagen, 1861), and Neoneura confundens Wasscher & van't Bosch for Formosa province;Rhionaeschna planaltica (Calvert), Erythemis plebeja (Burmeister), Erythrodiplax nigricans(Rambur, 1842) and Progomphus aberrans Belle for San Luis province; Planiplaxerythropyga (Karsch 1891), Homeoura chelifera (Selys, 1876) and Oxyagrion brevistigmaSelys, 1876 for Córdoba province; Tigriagrion aurantinigrum Calvert for Corrientes province;and Acanthagrion minutum Leonard and Telebasis willinki Fraser for Misiones province.